Characterization of R2∗ and tissue density in the human lung: Application to neonatal imaging in the intensive care unit. Issue 2 (19th December 2019) - Hahn, Andrew D.; Malkus, Annelise; Kammerman, Jeffery; Higano, Nara; Walkup, Laura; Woods, Jason; Fain, Sean B.
Abstract : Purpose: Novel demonstration of R 2 ∗ and tissue density estimation in infant lungs using 3D ultrashort echo time MRI. Differences between adult and neonates with no clinical indication of lung pathology is explored, as well as relationships between parameter estimates and gravitationally dependent position and lung inflation state. This provides a tool for probing physiologic processes that may be relevant to pulmonary disease and progression in newborns. Methods: R 2 ∗ and tissue density were estimated in a phantom consisting of standards allowing for ground truth comparisons and in human subjects ( N = 5 infants, N = 4 adults, no clinical indication of lung dysfunction) using a 3D radial multiecho ultrashort echo time MRI sequence. Whole lung averages were compared between infants and adults. Dependence of the metrics on anterior‐posterior position as well as between end‐tidal inspiration and expiration were explored, in addition to the general relationship between R 2 ∗ and tissue density. Results: Estimates in the phantom did not differ significantly from ground truth. Neonates had significantly lower mean R 2 ∗ ( P = .006) and higher mean tissue density ( P = 1.5e‐5) than adults. Tissue density and R 2 ∗ were both significantly dependent on anterior‐posterior position and lung inflation state ( P < .005). An overall inverse relationship was found between R 2 ∗ and tissue density, which was similar in both neonates and adults. Conclusion: Estimation of tissue density and R 2 ∗ in free breathing, nonsedated, neonatal patients is feasible using multiecho ultrashort echo time MRI. R 2 ∗ was no different between infants and adults when matched for tissue density, although density of lung parenchyma was, on average, lower in adults than neonates.